A nation within : Navajo land and economic development - Rosser, Ezra (Cambridge : Cambridge University Press, 2021)
In A Nation Within, Ezra Rosser explores the connection between land-use patterns and development in the Navajo Nation. Roughly the size of Ireland or West Virginia, the Navajo reservation has seen successive waves of natural resource-based development over the last century: grazing and over-grazing, oil and gas, uranium, and coal; yet Navajos continue to suffer from high levels of unemployment and poverty. Rosser shows the connection between the exploitation of these resources and the growth of the tribal government before turning to contemporary land use and development challenges. He argues that, in addition to the political challenges associated with any significant change, external pressures and internal corruption have made it difficult for the tribe to implement land reforms that could help provide space for economic development that would benefit the Navajo Nation and Navajo tribal members.
The Navajo Nation -- A new and old deal for Navajos : oil and sheep -- War production and growing pains : uranium and coal -- Alternative environmental paths -- Golf balls and discretionary funds -- Improving Tribal governance -- Locally grounded development -- Reclaiming the land -- Creating space for experimentation -- Sovereign assertions.
Title from publisher's bibliographic system (viewed on 27 Sep 2021).
Keywords: Law and economic development -- Navajo Nation, Arizona, New Mexico & Utah; Navajo Indians -- Economic conditions; Navajo Nation, Arizona, New Mexico & Utah -- Economic conditions